Impact of Chavez’s Misiones in the Venezuelan economic crisis - Solano Pinero, Luis Alberto (2023)
The master thesis deals with the real impact of the social programs in Venezuela applied during Chavez’s administration and analyzes the historical context of Venezuela that pushed and inspired the former president to implement and make such drastic changes in the Venezuelan social, healthcare, and educational system. Venezuela it’s the country with the highest oil reserves in the world yet is struggling with the highest hyperinflation in the world, a big social and political instability. The thesis seeks to find the relationship between the fiscal and monetary policy implemented in the country with the social programs applied by Chavez and his successor Maduro, to allow the reader to understand the lack of sustainability of the programs. In addition, tries to create a relationship between data provided by the Venezuelan government and other 3rd parties such as journalists, non-governmental organizations, or other independent researchers.